2020
DOI: 10.1021/acs.chemrev.9b00583
|View full text |Cite
|
Sign up to set email alerts
|

Helical Anion Foldamers in Solution

Abstract: Using anions to induce molecular structure is a rapidly growing area of dynamic and switchable supramolecular chemistry. The emphasis of this review is on helical anion foldamers in solution, and many of the beautiful complexes described herein are accentuated by their crystal structures. Anion foldamers are defined as single- or multistrand complexesoften helicalthat incorporate one or more anions. The review begins by discussing foldamer structure and nomenclature and follows with discourse on the anions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 112 publications
0
63
0
Order By: Relevance
“…64 Foldamers consist of rather exible strands and form well-organized supramolecular structures with neutral and/or anionic guest molecules, and thus may be considered as an induced-t type receptor. [65][66][67] In fact, Moore and Drickamer et al demonstrated that binding constants (K) of the piperazine or terpene guest upon interactions with oligo (m-phenylene ethynylene) foldamers in polymer matrixes decreased with increasing pressure of up to 65 000 MPa, i.e., positive reaction volumes (DV > 0), revealed by the diamond anvil cell technique. 68 Nevertheless, solution-state molecular recognition behavior of foldamers under hydrostatic pressures has not been examined in any detail, and hence, is still a challenge for the further evolution of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…64 Foldamers consist of rather exible strands and form well-organized supramolecular structures with neutral and/or anionic guest molecules, and thus may be considered as an induced-t type receptor. [65][66][67] In fact, Moore and Drickamer et al demonstrated that binding constants (K) of the piperazine or terpene guest upon interactions with oligo (m-phenylene ethynylene) foldamers in polymer matrixes decreased with increasing pressure of up to 65 000 MPa, i.e., positive reaction volumes (DV > 0), revealed by the diamond anvil cell technique. 68 Nevertheless, solution-state molecular recognition behavior of foldamers under hydrostatic pressures has not been examined in any detail, and hence, is still a challenge for the further evolution of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are dynamic and typically exist in an equilibrium of the folded and unfolded structure [20] . Anion templated foldamers have grown rapidly into an exciting field, and interested readers are encouraged to read the recent and comprehensive review by Berryman and co‐workers [21] …”
Section: Foldamersmentioning
confidence: 99%
“…We have proposed that the introduction of a helix-forming subunit together with additional two binding sites would allow us to bind all four oxygen atoms of the perrhenate anion. Recent analysis of the literature on helical anion foldamers shows that this kind of synthetic receptors demonstrates high selectivity even in an aqueous medium [46]. Preliminary quantum chemical modeling of the receptor structures revealed that dicarboxamide derivatives of ferrocene, m-xylylene, and diphenylacetylene are promising helix-forming subunits.…”
Section: Design and Synthesismentioning
confidence: 99%
“…demonstrates high selectivity even in an aqueous medium [46]. Preliminary quantum chemical modeling of the receptor structures revealed that dicarboxamide derivatives of ferrocene, m-xylylene, and diphenylacetylene are promising helix-forming subunits.…”
Section: Design and Synthesismentioning
confidence: 99%